Anti-POSTN and Anti-TIMP1 Autoantibodies as Diagnostic Markers in Esophageal Squamous Cell Carcinoma - Xie, Weihong; Sun, Guiying; Zhu, Jicun; Wang, Huimin; Han, Zhuo; Wang, Peng (Frontiers in Genetics, 2022)
Esophageal cancer is one of the most commonly diagnosed malignant gastrointestinal tumors. The study aims to explore the diagnostic values of anti-POSTN and anti-TIMP1 autoantibodies in esophageal squamous cell carcinoma (ESCC). Differentially expressed genes (DEGs) associated with esophageal cancer were screened out by LIMMA method in Gene Expression Profiling Interactive Analysis (GEPIA) platform. Search Tool for the Retrieval of Interacting Genes (STRING) was used to construct the protein-protein interaction (PPI) based on highly DEGs. The candidate hub genes were the intersection genes calculated based on degree and Maximal Clique Centrality (MCC) algorithms via Cytoscape. 370 participants including ESCC patients and matched normal controls were enrolled in enzyme-linked immunosorbent assay (ELISA) to detect the expression levels of autoantibodies corresponding to POSTN and TIMP1 proteins. A total of 375 DEGs with high expression were obtained in esophageal cancer. 20 hub genes were acquired using the cytoHubba plugin by degree and MCC algorithm, respectively. The expression levels of anti-POSTN and anti-TIMP1 autoantibodies were higher in sera of ESCC patients (P<0.05). Anti-POSTN autoantibody can diagnose ESCC patients with an AUC of 0.638 at the specificity of 90.27%, sensitivity of 27.57% and anti-TIMP1 autoantibody can diagnose ESCC patients with an AUC of 0.585 at the specificity of 90.27%, sensitivity of 20.54% (P<0.05). In addition, anti-POSTN and anti-TIMP1 autoantibodies can distinguish ESCC patients from normal controls in most clinical subgroups (P<0.05). In conclusion, anti-POSTN and anti-TIMP1 autoantibodies may be potential biomarkers in the clinical diagnosis of ESCC.